2021
DOI: 10.1002/ptr.6990
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nigella sativa oil extract on cardiometabolic risk factors in type 2 diabetes: A randomized, double‐blind, placebo‐controlled clinical trial

Abstract: The objective of this study was to determine the effects of Nigella sativa oil extract on cardiometabolic risk factors in people with type 2 diabetes (T2D). A randomized, controlled, clinical trial was conducted on 43 patients with T2D (23 women and 20 men; aged 53.5 ± 7.4 years). The intervention group (N = 23) received two 500-mg per day soft gel capsules containing Nigella sativa oil extract and the control group (N = 20) received two identical placebo soft gel capsules containing sunflower oil per day for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
58
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 38 publications
0
58
0
2
Order By: Relevance
“…Titles and abstracts were examined for all the remaining 633 records, resulting in the exclusion of 572 publications. Next, the full texts for 61 RCTs were checked, and 50 records were excluded for the following reasons: three studies investigated the effects of N. sativa combining with other supplements where the independent effect of N. sativa could not be distinguished ( 31 – 33 ); three studies had non-randomized designs ( 34 – 36 ); one study reported its results in a non-English language ( 37 ); two studies did not have an appropriate control group ( 38 , 39 ); and the 41 remaining publications provided insufficient data and/or did not meet the inclusion criteria. The final quantitative analysis included 11 trials with 666 participants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Titles and abstracts were examined for all the remaining 633 records, resulting in the exclusion of 572 publications. Next, the full texts for 61 RCTs were checked, and 50 records were excluded for the following reasons: three studies investigated the effects of N. sativa combining with other supplements where the independent effect of N. sativa could not be distinguished ( 31 – 33 ); three studies had non-randomized designs ( 34 – 36 ); one study reported its results in a non-English language ( 37 ); two studies did not have an appropriate control group ( 38 , 39 ); and the 41 remaining publications provided insufficient data and/or did not meet the inclusion criteria. The final quantitative analysis included 11 trials with 666 participants.…”
Section: Resultsmentioning
confidence: 99%
“…All the included trials had parallel designs and were published between 2012 and 2022. These studies were carried out in Iran ( 19 , 21 , 37 , 41 , 43 , 45 , 46 ), India ( 40 , 44 ), Egypt ( 20 ), and Saudi Arabia ( 42 ). In total, 666 participants (338 interventions and 328 controls) were recruited with the age range between 42.9 ± 3.2 and 56 ± 3.4 years old and the BMI range between 26.79 ± 2.94 and 33.90 ± 2.10 kg/m 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous study, intervention with N. sativa oil for 2 months was able to have beneficial effects on glycemic control, lipid profile, blood pressure and body weight in diabetic patients (Hadi et al, 2021). In another study, 2 months intervention in patients with rheumatoid arthritis increased plasma levels of interleukin‐10 as an anti‐inflammatory cytokine and also showed antioxidant properties (Hadi et al, 2016).…”
Section: Discussionmentioning
confidence: 95%
“…Overall, the effects of the black seed oil and vitamin E on the reproductive functions could vary depending on the dosages and duration of the treatment. However, most of the human trials of black seed oil also used doses similar to this study (Hadi et al, 2021;Koshak et al, 2021).…”
Section: Discussionmentioning
confidence: 99%